Przepisy porządkowe na zjazdach elekcyjnych w latach 1587–1674 - Kucharski, Tomasz (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> Present article concerns the provisions about the security and order during the election of the king in Both Nations Commonwealth, which were designed to ensure the safe and lawful carrying out election conventions. The purpose of these provisions was guaranteeing: proper organization of the meeting of Legislature (known as The Circle of Knights), correct adoption of foreign envoys and lawful conduct of monarch election. These regulations were prepared to fi ght with the criminal off ences and assurance the legal instruments to cope with problems concerning with functioning security services, building infrastructural facilities and supplying food. The author points at heterogenic nature of provisions of the security and order during the election of the polish kings, which included both procedural as well as substantive rules. Furthermore, substantive rules were related not merely with the criminal provisions, but also the others, similar to present-day regulations, which secure the mass events. The author tries to present the process of preparation and implementation of the provisions about the security and order during the election of the polish kings as one of the main tasks in the process of organization of the election conventions. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->